Demographic Headwinds in Central and Eastern Europe - Batog, Cristina (Departmental Papers; Departmental Paper, 2019)
The populations of Central and Eastern European (CESEE) countries-with the exception of Turkey-are expected to decrease significantly over the next 30 years, driven by low or negative net birth rates and outward migration. These changes will have significant implications for growth, living standards and fiscal sustainability.